Deep learning implementation in mentawai vocational schools: pedagogical readiness, educational technology utilization, and institutional support - Heri Noviko; Muhammad Adri; M. Giatman; Hendra Hidayat (Global Econedu, 2026)
This study examined the contributions of teachers’ pedagogical readiness and educational technology utilization to deep learning implementation through institutional support in public vocational schools in the Mentawai Islands Regency. An explanatory cross-sectional survey targeted all 70 teachers, with 65 complete responses analyzed using PLS-SEM. Pedagogical readiness contributed significantly to deep learning implementation (β = 0.330, p = 0.034) and institutional support (β = 0.456, p = 0.007). Educational technology utilization did not contribute significantly to deep learning implementation or institutional support. Institutional support also showed no significant direct contribution to deep learning implementation and did not mediate the relationships involving pedagogical readiness or educational technology utilization. These findings identify pedagogical readiness as the most consistent factor in the model. Strengthening teachers’ pedagogical competence, aligning technology use with instructional objectives, and translating institutional support into concrete instructional assistance are important for improving deep learning practices in geographically remote vocational schools.